Civil Society, Philanthropy, and the Fate of the Commons. - Sievers, Bruce R. (Civil Society: Historical and Contemporary Perspectives., 2010)
Traces the historical development of civil society and philanthropy in the West and analyzes their role in solving the problems faced by modern liberal democracy.